The association of Carbohydrate Quality Index with cardiovascular disease risk factors among women with overweight and obesity: A cross-sectional study - Khosravinia, Darya; Shiraseb, Farideh; Mirzababaei, Atieh; Daneshzad, Elnaz; Jamili, Shahin; Clark, Cain C. T.; Mirzaei, Khadijeh (Frontiers in Nutrition, 2022)
Background: Diet is one of the most important factors influencing cardiovascular disease (CVD). The negative relationship between carbohydrate intake with lipid profiles and body weight have been previously investigated. However, this is the first study seeking to assess the association of carbohydrate quality index (CQI) with CVD risk factors. Materials and Methods: This cross-sectional study was conducted on 291 Iranian overweight and obese women, with a body mass index (BMI) ranging between 25 and 40 kg/m2, and aged 18 to 48 years. CQI scores were calculated by using a validated 147-item semi-quantitative food frequency questionnaire (FFQ). Biochemical and anthropometric measures were assessed using standard methods, and bioelectrical impedance was used to measure body composition. Results: We observed that fruits (P<0.001), vegetables (P<0.001), and protein (P=0.002) intake were higher in participants with a higher score of the CQI. When we adjusted for potential confounders, we observed that the CQI was negatively related to systolic blood pressure (SBP) (β=-6.10; 95% CI=-10.11, -2.10; P=0.003) and DBP (β=-3.11; 95% CI=-6.15, -0.08; P=0.04). Also, greater adherence to a high CQI dietary pattern, compared to the reference group, was negatively related to HOMA-IR (β=-0.53; 95% CI=-0.94, -0.12) (P for trend=0.01), WC (β=-3.18; 95% CI=-6.26, -0.10) (P for trend=0.04), waist-hip ratio (WHR) (β=-0.01; 95% CI=-0.03, -0.001) (P for trend=0.03), BMI (β=-1.21; 95% CI=-2.50, 0.07) (P for trend=0.06), and BF (β=-2.06; 95% CI=-3.82, -0.30) (P for trend=0.02). Conclusion: In line with previous studies, the CQI was inversely associated with blood pressure, WC, WHR, BMI, and BF. Further prospective and clinical trial studies are suggested to confirm these data.